Diversifications effect on firm's value in manufacturing sector in Malaysia / Shashazrina Roslan - Roslan, Shashazrina (2007)
This study focused on the diversification's effect on firm's value in manufacturing sector in Malaysia. The objective or purpose of this study is to determine whether there is an effect to the firm's value in diversifications. To analyze the diversification's affect, this study using sample of 50 companies which have been listed in Bursa Malaysia in industrial sector. The time horizon is during 2001 to 2006, which is six years. There are three variables have been used in this study which are earnings, assets and sales. The statistical test for this study is using multiple linear regression models to determine the significant effect on firm's value in diversifications. There are some previous researchers have concluded that there are significant effect on firm's value in diversification. There are also some of them says oppositely which there is insignificant effect. This study also can be use by the investors as their guideline to know the effect of the firm's value because of diversifications. The results show that only earnings give significant effects on firm's value in diversification.